Adjuvant electronic brachytherapy for endometrial carcinoma: a 4-year outcomes report - Sarria, Gustavo R.; Sperk, Elena; Wenz, Frederik; Schneider, Frank; Abo-Madyan, Yasser; Giordano, Frank Anton; Ehmann, Michael (Brachytherapy, 2020)
Purpose - The purpose of the study was to report the outcomes of a single-center adjuvant electronic brachytherapy (e-BT) experience for patients with endometrial carcinoma. - Methods and Materials - Patients were retrospectively assessed. Intracavitary e-BT was applied through a cylindrical applicator (diameters 2.5-3.5 cm). e-BT single doses ranged between 4 and 7 Gy (EQD2 ∼ 6-12, α/β of 10 Gy and an relative biological effectiveness of 1.3) at 5-mm depth. Adverse events are reported at first week, 1-3 months, 3-12 months, 12-24 months, and >24 months. The overall survival, disease-free survival, distant disease control rate, and local control rate were estimated using the Kaplan-Meier method. - Results - Twenty-nine patients were assessed. The median age was 68 [48-86] years. External beam radiotherapy was added in n = 8 (27.6%) patients. Staging was 13.8% for T1a, 51.7% for T1b, 24.1% for T2, 6.9% for T3a, and 3.4% for T3b. Grading was G3 in 51.7% (n = 15), G2 in 20.7% (n = 6), and G1 in 27.6% (n = 8). Median followup was 47 months [5-88]. Overall Grade 1, 2, and 3 toxicity was 89.7% (n = 26), 17.2% (n = 5), and 6.9% (n = 2), respectively. No Grade 3 cystitis or proctitis or any Grade 4 or 5 toxicity occurred during followup. No local recurrences were detected. Estimated distant disease control rate was 92.1% (n = 2, distant metastasis at 7 and 11 months). Estimated 4-year overall survival was 84.8% (n = 4 events, two unrelated to disease) and disease-free survival was 84.6%. - Conclusions - Our data suggest that e-BT resembles a very-low-toxicity profile and a high local control rate in the adjuvant scenario for patients with endometrial carcinoma.
Gesehen am 08.12.2025